Quadrivalent meningococcal serogroups A, C, W, and Y tetanus toxoid conjugate vaccine (MenACWY-TT): a review. (December 2013) - Ghanem, Soha; Hassan, Sara; Saad, Randa; Dbaibo, Ghassan S
<x xml:space="preserve">Abstract</x> Introduction: Meningococcal disease poses serious health risks globally. The six Neisseria meningitidis serogroups responsible for most of the disease burden are A, B, C, W, X and Y. The case fatality rate remains high worldwide and prevention by vaccination remains the best strategy. Because polysaccharide vaccines are poorly immunogenic in young children, conjugated vaccines were developed to overcome this drawback. The quadrivalent meningococcal conjugate vaccine (MenACWY-TT), comprising the serogroups A, C, W and Y conjugated to tetanus toxoid carrier protein (marketed under the trade name <ext-link ext-link-type="uri" xlink:href="http://informahealthcare.com/action/doSearch?type=advanced&displaySummary=true&displaySummary=true&field1=keywords&text1=Nimenrix&logicalOpe1=OR&field2=articletitle&text2=Nimenrix&logicalOpe2=AND&field3=all&text3=&search=Search&categoryId=41010274&categoryId=40002416&categoryId=40004717&categoryId=40004717&filter=multiple&AfterMonth=1&AfterYear=&BeforeMonth=12&BeforeYear=&sortBy=date&nh=20" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink">Nimenrix™), is the first quadrivalent vaccine to be approved in Europe as a single dose for ages 12 months and in Canada for ages 12 months to 55 years. Areas covered: This review addresses the limitations posed by polysaccharide vaccines, compares them with the MenACWY-TT conjugated alternative, and focuses on the clinical studies that investigate the immunogenicity and reactogenicity of MenACWY-TT in various age groups and its co-administration with other vaccines compatible with each age group. Expert opinion: Evidence suggests that MenACWY-TT has a good immunogenicity profile across a broad age range including toddlers, children, adolescents, and adults. It also has an acceptable safety profile and is well tolerated when administered with other vaccines.